2019
DOI: 10.1029/2019gl083273
|View full text |Cite
|
Sign up to set email alerts
|

An Index to Better Estimate Tropical Cyclone Intensity Change in the Western North Pacific

Abstract: A revised predictor called the net energy gain rate (NGR) is suggested by considering wind‐dependent drag coefficient based on the existing maximum potential intensity theory. A series of wind speed‐dependent NGR, known as NGR‐w, is calculated based on pretropical cyclone (TC) averaged ocean temperatures from the surface down to 120 m (at 10‐m intervals) to include the TC‐induced vertical mixing for 13 years (2004–2016) in the western North Pacific. It turns out that NGR50‐w (NGR‐w based on temperature average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Lin et al [31] suggested DMPI using DAT instead of prestorm sea surface temperature to consider negative feedback by TC-induced sea surface cooling on existing SST-based MPI. DMPI has significantly reduced the overestimation of maximum intensity of the existing SST-based MPI and has frequently been used to predict TC intensity and RI [2,19,32,33]. The variables based on intensification potential (POT; MPI − initial intensity) were the essential factors in the CSTIPS-DAT model.…”
Section: Methodology 221 Static and Synoptic Potential Predictorsmentioning
confidence: 99%
“…Lin et al [31] suggested DMPI using DAT instead of prestorm sea surface temperature to consider negative feedback by TC-induced sea surface cooling on existing SST-based MPI. DMPI has significantly reduced the overestimation of maximum intensity of the existing SST-based MPI and has frequently been used to predict TC intensity and RI [2,19,32,33]. The variables based on intensification potential (POT; MPI − initial intensity) were the essential factors in the CSTIPS-DAT model.…”
Section: Methodology 221 Static and Synoptic Potential Predictorsmentioning
confidence: 99%
“…The qualitative differences between H 50 and H 75 are minor. H is often calculated to the depth of the 26°C, but TC intensity change in the deep ocean is better correlated with metrics including either a depth‐mean T , an integration of T over a fixed depth, or stratification (Lee et al, ; Price, ; Vincent et al, ).…”
Section: Datamentioning
confidence: 99%
“…Numerous attempts have been made to predict 24 h TC intensity changes using empirical models as well as numerical modelling techniques [7]. In empirical prediction, much of the effort based on statistical-dynamical approaches has gone towards improving TC intensity forecasts via nonlinear approaches using new or optimized predictors [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In empirical prediction, much of the effort based on statistical-dynamical approaches has gone towards improving TC intensity forecasts via nonlinear approaches using new or optimized predictors [8,9]. Finding and utilizing new predictors that accurately represent TC intensity changes can help to improve the forecasting performance of statistical-dynamical models [7]. For numerical models, different parameterization schemes can be adopted to achieve obvious and unique results in terms of performance and characteristics [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation